Interleukin-1 beta and transforming growth factor-beta cooperate to induce neurosphere formation and increase tumorigenicity of adherent LN-229 glioma cells - Wang, Lei; Liu, Ziyan; Balivada, Sivasai; Shrestha, Tej Bahadur; Bossmann, Stefan H.; Pyle, Marla; Pappan, Loretta; Shi, Jishu N.; Troyer, Deryl L. (My University, 2012)
Introduction: Glioma stem cells (GSCs) have the property of self-renewal and appear to be a driving force for the initiation and recurrence of gliomas. We recently found that the human tumorigenic LN-229 glioma cell line failed to form neurospheres in serum-free conditions and generated mostly small tumors in vivo, suggesting that either LN-229 GSCs are not active in these conditions or GSCs are absent in the LN-229 cell line. Methods: Using self-renewal assay, soft-agar colony assay, cell proliferation assay, invasion assay, real time PCR analysis, ELISA and in vivo tumorigenic assay, we investigated the effects of interleukin (IL)-1beta and transforming growth factor (TGF)-beta on the development of GSCs from LN-229 cells. Results: Here, we demonstrate that the combination of IL-1beta and TGF-beta can induce LN-229 cells to form neurospheres in serum-free medium. IL-1beta/TGF-beta-induced neurospheres display up-regulated expression of stemness factor genes (nestin, Bmi-1, Notch-2 and LIF), and increased invasiveness, drug resistance and tumor growth in vivo: hallmarks of GSCs. These results indicate that IL-1beta and TGF-beta cooperate to induce a GSC phenotype in the LN-229 cell line. Induction of nestin, LIF and Notch-2 by IL-1beta/TGF-beta can be reverted after cytokine withdrawal. Remarkably, however, up-regulated Bmi-1 levels remained unchanged after cytokine withdrawal; and the cytokine-withdrawn cells maintained strong clonogenicity, suggesting that Bmi-1 may play a crucial role in tumorigenesis. Conclusions: Our finding indicates that glioma cells without self-renewal capability in standard conditions could also contribute to glioma malignancy when cytokines, such as IL-1beta and TGF-beta, are present in the tumor environment. Targeting GSC-promoting cytokines that are highly expressed in glioblastomas may contribute to the development of more effective glioma therapies.
Keywords: Glioma stem cells; Interleukin-1 beta; Transforming growth factor-beta; Neurosphere formation; Tumorigenicity